Redescription of two rare, deep-sea species of hyperiidean amphipod, Lanceola loveni antarctica Vinogradov, 1962 and L. sphaerica Vinogradov, 1970 (Crustacea: Amphipoda: Hyperiidea: Lanceolidae) - Zeidler, Wolfgang (Zootaxa, 2021)
Lanceola loveni antarctica and L. sphaerica are rare deep-sea species known from very few specimens. Until recently (Zeidler 2019) L. loveni antarctica was known only from the types, seven specimens (7–27 mm), from the Indian Ocean Sector of the Antarctic (Vinogradov 1962). Similarly, L. sphaerica, originally described as a variety of L. clausi (Vinogradov, 1957), based on two damaged specimens, a female (8.0 mm) and a male (9 mm), from the Kurile-Kamchatka region of the NW Pacific, later elevated to full species status by Vinogradov (1970) upon the discovery of a well-preserved male (5 mm) from the same general region, was until then known only from these three specimens. The recent discovery of several specimens of both species in the USNM (Zeidler 2019) has now made it possible to provide a more detailed redescription of these rare species, including some new distribution records.